Polysaccharides of Atractylodes Macrocephala Koidz Alleviate LPS-Induced Bursa of Fabricius Injury in Goslings by Inhibiting EREG Expression - Shuying Gong; Bingqi Zhang; Xiang Sun; Weijun Liang; Longsheng Hong; Xiang Zhou; Wanyan Li; Yunbo Tian; Danning Xu; Zhongping Wu; Bingxin Li (Animals)
The bursa of Fabricius (BF) plays crucial roles in the goslings’ immune system. During waterfowl breeding, the presence of lipopolysaccharides (LPSs) in the environment can induce inflammatory damage in geese. Polysaccharides of Atractylodes macrocephala Koidz (PAMKs), as the main active component of the Chinese medicine Atractylodes macrocephala, have significant immune-enhancing effects. Accordingly, this study intended to investigate the effect of PAMKs on LPS-induced BF injury in goslings. Two hundred 1-day-old goslings (half male and half female) were selected and randomly divided into control, PAMK, LPS, and PAMK + LPS groups. The control and LPS groups were fed the basal diet, and the PAMK and PAMK + LPS groups were fed the basal diet containing PAMKs at 400 mg/kg. The goslings in the LPS and PAMK + LPS groups were injected intraperitoneally with LPS at a concentration of 2 mg/kg on days 24, 26, and 28 of this study. The control and PAMK groups were injected with equal amounts of saline. On the 28th day, 1 h after the LPS injection, the BF and serum were collected and analyzed for organ indices, cytokines, antioxidant indicators, and histological observations. Histological examination and HE staining demonstrated that the PAMK treatment ameliorated the LPS-induced BF atrophy, structural damage, increased cellular exudation, and reticulocyte hyperplasia in the goslings. The cytokine and antioxidant marker analyses in the BF cells demonstrated that the PAMK treatment mitigated the LPS-induced increase in the interleukin-1β (IL-1β), malondialdehyde (MDA), and inducible nitric oxide synthase (iNOS) levels, as well as the decrease in the transforming growth factor-β (TGF-β) and superoxide dismutase (SOD) activities. Further transcriptome sequencing identified a total of 373 differentially expressed genes (DEGs) between the LPS and PAMK + LPS groups. The KEGG enrichment pathway analysis showed that the DEGs were significantly enriched in the Toll-like receptor, p53, MAPK, GnRH, and ErbB signaling pathways. Among them, EREG played key roles in the activation of the MAPK, GnRH, and ErbB signaling pathways. Further research showed that the addition of PAMKs significantly inhibited the LPS-induced EREG expression, increased the cell viability, promoted the cell cycle entry into the S and G2 phases, and inhibited apoptosis. Meanwhile, PAMKs can reduce the protein expression of p-JNKs and c-FOS by inhibiting EREG. In summary, this study found that PAMKs could alleviate LPS-induced BF injury in goslings by inhibiting the expression of EREG.